2007
DOI: 10.1073/pnas.0700042104
|View full text |Cite|
|
Sign up to set email alerts
|

Strategy for reversing resistance to a single anticancer agent in human prostate and pancreatic carcinomas

Abstract: Effective therapies for most solid cancers, especially those that have progressed to metastasis, remain elusive because of inherent and acquired resistance of tumor cells to conventional treatments. Additionally, the effective therapeutic window for many protocols can be very narrow, frequently resulting in toxicity. The present study explores an anticancer strategy that effectively eliminates resistant cancer cells without exerting deleterious effects on normal cells. This approach employs melanoma differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
43
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 38 publications
1
43
0
Order By: Relevance
“…IL24 is able to efficiently induce apoptosis in a wide variety of human cancers except pancreatic and ovarian cancer [21]. IL24 does not significantly alter growth or induce apoptosis in human pancreatic cancer cells due to the expression of oncogenic K-ras, which is a common genetic alteration in pancreatic cancers.…”
Section: Combination Therapy With Il24mentioning
confidence: 99%
See 1 more Smart Citation
“…IL24 is able to efficiently induce apoptosis in a wide variety of human cancers except pancreatic and ovarian cancer [21]. IL24 does not significantly alter growth or induce apoptosis in human pancreatic cancer cells due to the expression of oncogenic K-ras, which is a common genetic alteration in pancreatic cancers.…”
Section: Combination Therapy With Il24mentioning
confidence: 99%
“…This resistance for IL24 can be overcome by combination treatment with an antisense K-ras expression vector. Another way to overcome the problem is to use IL24 in combination with non-toxic doses of a chemical compound from the endoperoxide class [21]. It has been reported that IL24 is able to induce apoptosis in ovarian cancer cells with a low efficiency.…”
Section: Combination Therapy With Il24mentioning
confidence: 99%
“…46 Apoptosis induction by mda-7/IL-24 also involves oxidative stress by generation of reactive oxygen species (ROS) specifically in cancer cells. 16,47,48 Initial studies in prostate cancer cells identified ROS as an active component in mda-7/IL-24 induced apoptosis. Antioxidants and mitochondrial permeability transition inhibitors hinder Ad.mda-7-mediated apoptosis and mitochondrial changes in prostate cancer cells.…”
Section: Diverse Molecular and Signal Transduction Pathways Involved mentioning
confidence: 99%
“…[39][40][41] Interestingly, agents that induce ROS generation, such as arsenic trioxide or endoperoxides, can also overcome the translational inhibition without altering K-ras expression. 25,27 Ad.mda-7-mediated apoptosis induction involves downregulation of the anti-apoptotic proteins Bcl-2 and Bcl-xL and upregulation of the pro-apoptotic proteins Bax and Bak. Prostate cancer cells stably overexpressing Bcl-2 or Bcl-xL, a frequent event in patients, acquire resistance to Ad.mda-7.…”
mentioning
confidence: 99%
“…Apoptosis induction by mda-7/IL-24 also involves oxidative stress by generation of reactive oxygen species (ROS) specifically in cancer cells. [25][26][27] The molecular mechanism of the cancer-selective apoptosis induction by mda-7/IL-24 remains to be unraveled. However, current studies highlight the ability of MDA-7/IL-24 to induce apoptosis selectively in cancer cells by altering diverse signaling pathways and processes in tumor and surrounding cells (Fig.…”
mentioning
confidence: 99%